Epistemology of Misyar Marriage by Yusuf al-Qaradawi in the Book of Zawāj al-Misyär Hakikatuh and Hukmuh from the Perspective of the Philosophy of Science - Mardi, Isra; Kodir, Abdul; Rohanda, Rohanda (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
Misyar marriage is a controversial alternative marital form within contemporary Islamic discourse, particularly concerning its legal validity and alignment with the objectives of Islamic law (maqāṣid al-sharīʿah). Imam Yusuf al-Qaradawi, a leading figure in modern Islamic legal thought, addresses this phenomenon in his work Zawāj al-Misyār Ḥaqīqatuh wa Ḥukmuh. This article seeks to examine the epistemological foundation of al-Qaradawi’s view on misyar marriage to understand the structure of his legal reasoning and methodology. This study specifically focuses on the epistemic foundations underlying Yusuf al-Qaradhawi's views on the practice of misyar marriage, the ijtihad method used, examining the authoritative sources that are Yusuf al-Qaradhawi's main references, and his approach in combining normative texts with contemporary social realities. This study adopts a qualitative descriptive-analytical method, employing content analysis of al-Qaradawi’s primary work, especially Zawāj al-Misyār Ḥakīkatuh wa Ḥukmuh. The analysis is conducted within the framework of Islamic philosophy of knowledge, emphasizing the integration of epistemologies. The findings reveal that al-Qaradawi constructs his fatwa through an integrative approach responsive to modern realities, employing takyīf fiqhī as a contextual ijtihad tool. His epistemic foundation combines scriptural authority with maqāṣid-oriented reasoning, producing legal opinions that are both normatively valid and socially constructive. This contributes significantly to the development of a adaptive contemporary Islamic legal epistemology and maslahah.